ASSESSMENT OF SOME FACTORS FOR SHOOT PROLIFERATION POTENTIAL IN TUBER EXPLANTS OF Gloriosa superba L. - A HIGH VALUE INDUSTRIAL MEDICINAL HERB (Applied Biological Research, 2023)
Gloriosa superba L., an important medicinal plant, is included in the list  of endangered plants so needs a special attention for its conservation  through micropropagation. An efficient in vitro regeneration protocol was  established using tubers as explants. Briefly, surface sterilized explants  were cultured on MS medium containing different concentrations and  combinations of 6-benzylaminopurine (BAP), kinetin and 1-naphthal eneacetic acid. Highest shoot regeneration frequency (88%) was recorded  in MS medium containing 2.0 mg L-1 BAP. Half strength MS media supplemented with indole-3-acetic and indole-3-butyric acid (IBA), either  alone or in combination, were used for rooting. Highest root regeneration (71%) was recordein 2.0 mg L-1IBA. Genetic fidelity of in vitro-raised  plants was evaluated using RAPD and ISSR molecular markers, as there  is always a danger of somaclonal variations in tissue culture technology. Out of the 17 (10 random amplified polymorphic DNA (RAPD) and 7 inter simple sequence repeats (ISSR) primers screened, 2 RAPD and 2  ISSR primers produceclear, distinct and reproducible amplicons. The  results revealed genetic homogeneity and true-to-type nature of in vitro raised plants using RAPD and ISSR analysis. The developed protocol  may prove helpful in regenerating valuable resource material for easy  growth.
Keywords: Explant; genetic fidelity; Gloriosa superba; micro propagation; molecular markers